CYP2D6 genotype and tamoxifen response for breast cancer: a systematic review and meta-analysis. - Danny W K Lum; Pablo Perel; Aroon D Hingorani; Michael V Holmes (PLoS ONE, 2013)
Objective To evaluate evidence on the association between CYP2D6 genotype and tamoxifen response through. Design Systematic review and meta-analysis of prospective, cross-sectional and case-control studies published to 2012. For each study, relative risks and 95% confidence intervals were extracted and pooled with a fixed and random effects model. Heterogeneity, publication bias, subgroup, and meta-regression analyses were performed. Data sources PubMed (inception-2012) and EMBASE (inception-2012). Eligibility criteria for selecting studies Criteria for inclusion were studies reporting breast cancer outcomes in patients treated with tamoxifen and genotyped for polymorphisms in the CYP2D6 gene. Results Twenty-five studies of 13,629 individuals were identified, of which 22 investigated the association of CYP2D6 genotype with outcomes in breast cancer women all receiving tamoxifen treatment ("treatment-only" design). Three randomized trials evaluated the effect of CYP2D6 genotype on tamoxifen response ("effect modification" design). In analysis of treatment-only studies, the relative risk (RR) of all-cause mortality (>307 events in 4,936 patients) for carriers of a CYP2D6 reduced function allele was 1.11 (95% confidence interval (CI): 0.94 to 1.31) compared to individuals with normal/increased function CYP2D6 alleles. When we investigated a composite outcome including all-cause mortality and surrogate endpoints for overall survival (>307 events in 6,721 patients), carriers of a CYP2D6 reduced function allele had a RR of 1.27 (95% CI: 1.11 to 1.45). From two randomized trials that permitted effect-modification analysis, one had only 154 patients and showed evidence of effect modification of tamoxifen by CYP2D6 genotype for distant recurrence but was directionally opposite to that predicted, whereas a larger trial of 2,537 patients failed to show evidence of effect modification for breast cancer-free interval (P values for interaction 0.02 and 0.44, respectively). Conclusions Based on these findings, there is insufficient evidence to recommend CYP2D6 genotyping to guide tamoxifen treatment.